2018
DOI: 10.29313/gmhc.v6i3.3618
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics Used for Upper Respiratory Tract Infection: a Case Study at a Primary Health Center Bogor Indonesia

Abstract: Acute upper respiratory tract infection (URTI) is one of the health problem in a community with high prevalence and healthcare cost. At the primary health center (PHC), URTI is one of the most common diseases with a prevalence 45.64% in Bogor city on 2015, while Basic Health Research 2013 data showed the prevalence of URTI in Indonesia by 25%. This study analyzes the antibiotic prescription for URTI patients, factors influencing the rationale of antibiotic prescriptions, and the rational use of medicine (RUM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
0
6
0
2
Order By: Relevance
“…These results are in line with those from our study, which found an increase of less susceptible isolates against oxacillin, tetracycline, trimethoprim-sulphamethoxazole, erythromycin, chloramphenicol, and clindamycin. Trimethoprimsulphamethoxazole and tetracycline are included in commonly used antibiotics to treat patients with respiratory infections in Indonesia [22][23][24]. This study provided an insight in pneumococcal colonization difference among HIV-infected children vaccinated with PCV7 that might be important for vaccination consideration for HIV children.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with those from our study, which found an increase of less susceptible isolates against oxacillin, tetracycline, trimethoprim-sulphamethoxazole, erythromycin, chloramphenicol, and clindamycin. Trimethoprimsulphamethoxazole and tetracycline are included in commonly used antibiotics to treat patients with respiratory infections in Indonesia [22][23][24]. This study provided an insight in pneumococcal colonization difference among HIV-infected children vaccinated with PCV7 that might be important for vaccination consideration for HIV children.…”
Section: Discussionmentioning
confidence: 99%
“…These data showed that penicillin might be the first choice of antibiotic for intrapartum prophylaxis and treatment of GBS infections [31]. In Indonesia, penicillin is still the most common antibiotic class consumed widely [32][33][34]. While there are occasional reports of penicillin resistance, resistance is so rare that penicillin can be safely used empirically [35].…”
Section: Plos Onementioning
confidence: 99%
“…Berdasarkan Pedoman Pengobatan Klinik yang dikeluarkan oleh Ikatan Dokter Indonesia (IDI), pada kasus rhinitis alergi, common cold dan laringitis dengan infeksi sekunder bakteri, pasien perlu mendapat tambahan antibiotika. Begitu pula pengobatan sinusitis dan otitis media akut diperlukan antibiotik dalam pengobatannya (Ambarwati, Setiawaty, and Wibowo 2018) (Thobari et al, 2019). Berdasarkan hal tersebut memungkinkan adanya peresepan antibiotik apabila dirasakan perlu untuk penyakitpenyakit tersebut.…”
Section: Hasil Dan Pembahasanunclassified